How to choose the world's top health diplomat. (28th October 2016) - Kickbusch, Ilona; Woods, Ngaire; Piot, Peter; Abbasi, Kamran
Abstract : Ilona Kickbusch and colleagues discuss the qualities required for the next director general of the World Health Organization